Realismo afetivo: evocar realismo além da representação - Karl Erik Schøllhammer (Estudos de Literatura Brasileira Contemporânea, 2012)
This essay will discuss different kinds of literary expression in search for ways to “realism” without giving continuity of the historical realism that appears during the 19th and 20th century. The focus is on literary experiences on the edges of representation aiming to develop strategies of performance and agency in search of effect and affects during its integral process of realization. Here the representative Realism is questioned by the commitment to the social reality of the object, on one hand, and, on the other, by the necessity to find creative strategies in relation to re- ality through literary and artistic activity. The ambition is to establish an aesthetic discussion of the strategic expressions of a reality that defies representation and questions the literary creativity and its possibility to create affective impacts and hereby accentuate its transforming potential in the contemporary Brazilian reality.